Increasing Empathy in Class X SMA 2 Batu Students Through Peer Counseling Training - Zahroh, Talya Mahmudatuz; Cahyani, Herlin; Zahra’ni, Farras Asma; Hotifah, Yuliati; Sulistyorini, Erna; Pratiwi, Awalya Siska (Proceedings Series of Educational Studies, 2024)
Empathy is not yet fully possessed by all students. Many students do not realize that empathy is very important to have. The presence of peer counseling in schools plays a crucial role because not all students are open to counseling with school counselors. This study aims to determine the effectiveness of peer counseling training in increasing empathy among high school students. The method used in this research is qualitative with a descriptive approach. The study was conducted at SMAN 2 Batu with tenth-grade students, involving a total of three student subjects. Data were collected through interviews after the subjects participated in peer counseling training. The results of the study concluded that peer counseling training is effective in increasing empathy among tenthgrade students at SMAN 2 Batu. This is evidenced by changes in several students who participated in the peer counseling training, where initially, the students did not have empathy for their peers or teachers, but after participating in the training, these students showed changes in understanding the importance of developing empathy